The Effect of Inoculation with Azotobacter on the Growth of Wheat and Tomato Plants - BADAWY, FARIDA H.; AMER, SAFIYA B. (The Libyan Journal of Agriculture, 2023)
Much of the interest in the non-symbiotic nitrogen fixing bacteria of the genus Azotobacter is due to the possibility of introducing it into soil and rhizosphere, by inoculation, to increase plant yield. Stimulation in rates of seed germination, root growth and plant development as a result of inoculation were reported by several investigators (1,3,5,7). Significant responses to azotobacter inoculation on yield of cereals and vegetable crops were also obtained (2,6). The objective of the present study was to test, under greenhouse conditions, the effect of Azotobacter inoculation on growth of wheat and tomato plants. Four strains of Azotobacter chroococcum Beijerinck isolated from the soil of the farm of Faculty of Agriculture, Tripoli, were used for preparing the inoculum. Pure cultures of the strains were grown in screw cap bottles on nitrogen-free sucrose agar medium of the following composition: K2HPO4 0.5 g, MgSO4 7H2O 0.2 g, NaCl 0.2 g, CaCI2 2H2O 0.1 g. NaMoO4 2H2O 0.01 g, MnSO4 4H2O trace, FeCI3 trace, sucrose 10 g. Agar 20 g, dist. water 1,000 ml. • After 10 days incubation at 30°C the surface growth formed was harvested by washing with sterile water and shaked to form a milky suspension of the azotobacter cells and cysts. Equal volumes of the suspensions of the four Azotobacter strains, adjusted to the same optical density, were mixed together to prepare the inoculum used. The experiments were conducted under greenhouse conditions in pots each containing 2 kg soil. The sandy soil used had a pH of 8.1 and contained 24.8% CaCO3 and 0.5% organic matter. Before planting, 3 g of superphosphate (20 % P2O5) were added to each pot and mixed thoroughly with the soil. One transplant of tomato (cultivar Homstead 24) or twenty seeds of wheat (cultivar Sidi El-Mesri 1) were planted in each pot. Azotobacter inoculation was made at the time of planting by pipetting one drop of inoculum on each seed of wheat or one ml per tomato transplant added directly to the roots before covering with the soil. Plants from uninoculated pots served as check (control). Five replicates were planted from each treatment in case of wheat and 8 replicates in case of tomato. After 5 weeks of growth, during which the pots were irrigated only with tap water, the plants were washed out with their roots, and length, fresh and dry weight of the plants of each pot were determined. The results obtained are presented in Tables 1 and 2. Farida H. Badawy, Department of Soil and Water, Faculty of Agriculture, University of Tripoli, Tripoli, Libya. Safiya B. Amer is a research assistant. Department of Soils and Water, Ministry of Agriculture, Benghazi, Libya.